2002
DOI: 10.1111/j.0014-3820.2002.tb00854.x
|View full text |Cite
|
Sign up to set email alerts
|

A Bird's-Eye View of the C-Value Enigma: Genome Size, Cell Size, and Metabolic Rate in the Class Aves

Abstract: Abstract. For half a century, variation in genome size (C-value) has been an unresolved puzzle in evolutionary biology. While the initial ''C-value paradox'' was solved with the discovery of noncoding DNA, a much more complex ''C-value enigma'' remains. The present study focuses on one aspect of this puzzle, namely the small genome sizes of birds. Significant negative correlations are reported between resting metabolic rate and both C-value and erythrocyte size. Cell size is positively correlated with both nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
181
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 220 publications
(195 citation statements)
references
References 74 publications
12
181
1
1
Order By: Relevance
“…Lungfishes, which survive long periods under hypoxic conditions, have very low metabolic rates and the largest genomes of all vertebrates (11). Although birds with their small genomes and small cells represent a wasteful strategy, even within this group small C-value correlates with short development time (24) and high metabolic rates (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lungfishes, which survive long periods under hypoxic conditions, have very low metabolic rates and the largest genomes of all vertebrates (11). Although birds with their small genomes and small cells represent a wasteful strategy, even within this group small C-value correlates with short development time (24) and high metabolic rates (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…A strong correlation between C-value and cell size exists, however (2,5). Within a taxon, smaller cells usually divide faster and have a higher metabolic rate, as evidenced by the strong negative correlation between specific metabolic rates corrected for body size and DNA amounts in mammals (6) and birds (7,8), and by direct measures of erythrocyte metabolism in amphibians (9). In birds there is a strong correlation between erythrocyte size and metabolic rate, with erythrocyte size correlating very strongly with cell sizes in other tissues (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The smallest amniote genome belongs to the pheasant (Phasianus colchicus; 0.97 pg). Indeed, no other group of amniotes has smaller or less variable genome size than birds (Tiersch & Wachtel, 1991;Gregory, 2002). When mapped onto the avian tree using a simple method like parsimony there is a strong signal of genome size homogeneity ( Figure 13.2), as suggested earlier by Waltari & Edwards (2002).…”
Section: Demise Of Repetitive Elements and Shrinking Genome Sizementioning
confidence: 73%
“…However, there are many reasons to predict that, despite the morphological and behavioral diversity of birds, genomic characters will show less variability than those seen in mammals. In fact, the uniformity of several aspects of the avian genome is already well documented, such as genome size and karyotype (Burt et al, 1999;Burt, 2002;Gregory, 2002;. The variation in traits such as total genome size and intron size have been examined across birds with varying degrees of taxon sampling and phylogenetic rigor, and some quantitative studies have shown that genome size is more constrained across birds than are other traits, such as basal metabolic rate, and shows signatures of stabilizing selection (Waltari & Edwards, 2002).…”
mentioning
confidence: 99%